2021
DOI: 10.3390/su132112090
|View full text |Cite
|
Sign up to set email alerts
|

Project Management in the Biotech Context: Exploring the Interrelation between Maturity and Sustainable Project Management

Abstract: Biotechnology is an emerging and increasingly important sector in the current context. As the number of biotech projects grows, so does the need to establish processes to improve project management effectiveness and project success, including assessing their impacts (positive and negative) on the Sustainable Development Goal (SDGs). This broader approach opens the door to developing a new project management (PM) paradigm designated by sustainable project management (SPM). However, there is a need for more empi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 53 publications
0
5
0
1
Order By: Relevance
“…Regardless of project's nature, conducting projects is the organization's way of generating the long-term investment goals of a company, which in its turn contributes to sustainability in a long-term perspective including SDGs (Magano et al, 2021). Recently, Banihashemi et al…”
Section: Related Empirical Literature and Research Hypothesis 251 Gpm...mentioning
confidence: 99%
See 1 more Smart Citation
“…Regardless of project's nature, conducting projects is the organization's way of generating the long-term investment goals of a company, which in its turn contributes to sustainability in a long-term perspective including SDGs (Magano et al, 2021). Recently, Banihashemi et al…”
Section: Related Empirical Literature and Research Hypothesis 251 Gpm...mentioning
confidence: 99%
“…However, projects generally consist of resembling activities and deliverables (Kerzner, 2022). Regardless of project's nature, conducting projects is the organization's way of generating the long-term investment goals of a company, which in its turn contributes to sustainability in a long-term perspective including SDGs (Magano et al, 2021). Recently, Banihashemi et al (2017) demonstrate the first quantification in the form of a model for integrating sustainability at each stage of PM practices.…”
Section: Related Empirical Literature and Research Hypothesismentioning
confidence: 99%
“…Such-outlined factors facilitate project management. resulting in reduced project costs and implementation time as well as in lesser reliance on rigid rules and procedures (Magano et al, 2021, as cited in Spalek, 2014Kerzner, 2019). Moreover.…”
Section: Originalitymentioning
confidence: 99%
“…carried out by J. Magano et al (2021) the majority of the respondents indicated that an organization's culture is characterized by informal project management.…”
Section: Originalitymentioning
confidence: 99%
“…W najnowszych tekstach zrównoważone zarządzanie projektami ma wymiar conditio sine qua non nowoczesnego rozumienia projektów w organizacjach (Whyte i in., 2022) oraz poza nimi, co coraz częściej adresowane jest poprzez dostrzeganie ich roli społecznej (Di Maddaloni i Sabini, 2022;Magano i in., 2021;Shen i in., 2010). Podejście do problemu może dotyczyć na przykład dojrzałości projektu i kształtowania relacji z interesariuszami oraz wpływu tych czynników na sukces projektu (Brajer-Marczak i in., 2021).…”
Section: Analiza Tematyczna Definicyjne Punkty Wyjścia W Dyskusjach O...unclassified